MEMORABILIA: OLD PHOTOGRAPHIC PROCESSES APPLICATION ON FUNCTIONAL OBJECTS - Alan Ridho Irezalnov; Irwandi Irwandi; Arti Wulandari (Specta: Journal of Photography, Arts, and Media, 2019)
Memorabilia: Old Photographic Process Application on Functional Objects. It is a concept of creating photographic artwork as a personal expression of memories that have passed for a long time, or have just been overlooked because they are triggered by an object or moment and are always ringing in the mind so that they bring back memories of the past. As one of several old photographic processes, Vandyke print is a photo printing technique in the nineteenth century with monochrome (sepia) color characters that fits perfectly with the old impression of representing memorabilia memories that are realized in visual form. In this creation, functional objects are used as photo print media. Material or objects used as media to express ideas are such as something impressive,  penetrating into feeling, thought, or action.  Generally  the material is understood to be passive, but on this context, things become active because they can trigger someone's memory of memorabilia. The works aim to bring back the memory of the past by printing old photographic processes by responding to functional objects which have personal stories and leave an impression. Apart from provoking the memories of the past, the photographic works could also become a personal reference of how important those memorabilia were.  Keywords: memorabilia, old photographic process, functional objects